OptiBench: An Optical Distance Measurement Test Bench Using Adaptive Algorithm With Sensor Fusion and Environmental Shielding - Kanchana Chathurangi Ahangama; Hemali Pasqual; Chinthaka Premachandra; H. Waruna Haripriya Premachandra (IEEE Access)
Optical Distance Measurement (ODM) systems have a wide range of applications in many sectors, including industrial, aerospace, and telecommunication. It is essential in systems where accuracy and reliability are critical. Environmental factors such as temperature fluctuations, humidity, and light intensity randomly affect the performance of ODM systems. The uncertainty of these natural factors makes it challenging to maintain the accuracy and reliability of ODM systems. This paper presents an innovative displacement test bench, OptiBench, that combines Adaptive Environmental Compensation (AEnC) algorithms, Multi-Sensor Fusion (MSF) techniques, and dynamic environmental shielding that improves ODM systems’ accuracy, precision, and robustness. The effectiveness of the OptiBench has been evaluated under a wide range of environmental conditions. The experimental result shows that it achieves a Mean Absolute Error (MAE) of 0.10 mm to 0.19 mm and precision values between 0.07 mm and 0.13 mm. The AEnC algorithm reduced temperature-induced errors from 0.25 mm to as low as 0.05 mm, and the MSF technique reduced the measurement variance from a range of 0.18 mm–0.47 mm2 (before fusion) to 0.12 mm–0.30 mm2 (after fusion), demonstrating its effectiveness in enhancing reliability and precision under varying environmental conditions. The Environmental Shielded Optical (ESO) system improved signal strength by up to 9 dB. Overall, the OptiBench system represents a significant advancement in optical distance measurement, providing a reliable, adaptable solution for applications where precision is paramount.